2020
DOI: 10.1097/sla.0000000000004566
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Risk Stratification and Outcomes in Children with Prenatally Diagnosed Lung Malformations

Abstract: Objective: The aim of this study was to assess current clinical outcomes in children with prenatally diagnosed congenital lung malformations (CLMs) and to identify prenatal characteristics associated with adverse outcomes. Summary Background Data: Despite a wide spectrum of clinical disease, the identification of fetal CLM subgroups at increased risk for hydrops and respiratory compromise at delivery has not been well defined. Methods: A retrospective cohort study was conducted using an operative database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…The overall perinatal prognosis of a fetus affected by the lung malformation is strongly associated with its overall growth during pregnancy rather than by its underlying histology (5). This concept has been supported in numerous studies, all which have shown that mass size, as opposed to type of lesion, is most predictive of perinatal outcome based on a variety of outcome measures, including fetal hydrops, neonatal respiratory symptoms, and likelihood of lung resection in the newborn period (5,20,22,23). The most common metric for lesion size is the CPAM volume ratio (CVR), which measures the three-dimensional size of the lesion relative to the fetal head circumference (24).…”
Section: Fetal Diagnosismentioning
confidence: 94%
See 4 more Smart Citations
“…The overall perinatal prognosis of a fetus affected by the lung malformation is strongly associated with its overall growth during pregnancy rather than by its underlying histology (5). This concept has been supported in numerous studies, all which have shown that mass size, as opposed to type of lesion, is most predictive of perinatal outcome based on a variety of outcome measures, including fetal hydrops, neonatal respiratory symptoms, and likelihood of lung resection in the newborn period (5,20,22,23). The most common metric for lesion size is the CPAM volume ratio (CVR), which measures the three-dimensional size of the lesion relative to the fetal head circumference (24).…”
Section: Fetal Diagnosismentioning
confidence: 94%
“…Approximately 70% of all congenital lung malformations are now detected during fetal anatomic survey (Figure 5) (20). While ultrasound is a useful tool for the detection of hyperechoic and cystic lung lesions, there is definite potential to misdiagnose primary fetal lung masses for other anomalies.…”
Section: Fetal Diagnosismentioning
confidence: 99%
See 3 more Smart Citations